Climbing the ladder: Determinants of access to and returns from higher education in Chile and Peru - Anja Gaentzsch; Gabriela Zapata-Román (United Nations Research Institute for Social Development (UNRISD), 2020)
In spite of large structural expansions in higher education in Chile and Peru during the 1980s and 1990s, and a favourable growth context, levels of inequality are still very high in both countries and inequities in higher education persist. This paper investigates the role that higher education has played for social mobility in Chile and Peru. In particular, to what extent circumstances determined at birth are associated with educational achievement, and how these circumstances have affected the access and returns to higher education, both vocational and university studies. Grounded in two conceptual approaches, human capital and equality of opportunity theories, the paper adopts a methodology of analysing secondary data sources from household surveys and administrative statistics in the two countries in order to present the picture of educational attainment in Chile and Peru, distribution of students to different types of tertiary education (public/private; vocational and technical/university) and differentiated by groups (male/female; indigenous/non-indigenous; rural/urban), as well as labour market returns. The paper finds that (i) circumstances that are beyond the control of individuals including parental education, ethnic background and geography are strong predictors for access to higher education; (ii) for those who do enter higher education, there are differential patterns of entry into public versus private institutions, and different streams of higher education; and (iii) returns to higher education are generally high, but differ strongly between groups and type of institution attended.
Keywords: 330; Access to higher education; returns of higher education; social mobility; equality of opportunity